The myxozoan minicollagen gene repertoire was not simplified by the parasitic lifestyle: computational identification of a novel myxozoan minicollagen gene - Kyslík, Jiří; Kosakyan, Anush; Nenarokov, Serafim; Holzer, Astrid S; Fiala, Ivan (BMC genomics, 2021)
BACKGROUND: Lineage-specific gene expansions represent one of the driving forces in the evolutionary dynamics of unique phylum traits. Myxozoa, a cnidarian subphylum of obligate parasites, are evolutionarily altered and highly reduced organisms with a simple body plan including cnidarian-specific organelles and polar capsules (a type of nematocyst). Minicollagens, a group of structural proteins, are prominent constituents of nematocysts linking Myxozoa and Cnidaria. Despite recent advances in the identification of minicollagens in Myxozoa, the evolutionary history and diversity of minicollagens in Myxozoa and Cnidaria remain elusive. RESULTS: We generated new transcriptomes of two myxozoan species using a novel pipeline for filtering of closely related contaminant species in RNA-seq data. Mining of our transcriptomes and published omics data confirmed the existence of myxozoan Ncol-4, reported only once previously, and revealed a novel noncanonical minicollagen, Ncol-5, which is exclusive to Myxozoa. Phylogenetic analyses support a close relationship between myxozoan Ncol-1-3 with minicollagens of Polypodium hydriforme, but suggest independent evolution in the case of the myxozoan minicollagens Ncol-4 and Ncol-5. Additional genome- and transcriptome-wide searches of cnidarian minicollagens expanded the dataset to better clarify the evolutionary trajectories of minicollagen. CONCLUSIONS: The development of a new approach for the handling of next-generation data contaminated by closely related species represents a useful tool for future applications beyond the field of myxozoan research. This data processing pipeline allowed us to expand the dataset and study the evolution and diversity of minicollagen genes in Myxozoa and Cnidaria. We identified a novel type of minicollagen in Myxozoa (Ncol-5). We suggest that the large number of minicollagen paralogs in some cnidarians is a result of several recent large gene multiplication events. We revealed close juxtaposition of minicollagens Ncol-1 and Ncol-4 in myxozoan genomes, suggesting their common evolutionary history. The unique gene structure of myxozoan Ncol-5 suggests a specific function in the myxozoan polar capsule or tubule. Despite the fact that myxozoans possess only one type of nematocyst, their gene repertoire is similar to those of other cnidarians.
Keywords: Myxozoa; Custom made script; Transcriptome; genom; Animals; Cnidaria; Life Style; Genome; životní styl; Phylogeny; Parasites; zvířata; fylogeneze; Taxonomically restricted genes; paraziti